2008
DOI: 10.1007/s11064-008-9712-y
|View full text |Cite
|
Sign up to set email alerts
|

The Promotive Effects of Thymosin β4 on Neuronal Survival and Neurite Outgrowth by Upregulating L1 Expression

Abstract: Thymosin beta(4) (Tbeta4) is a major actin-sequestering peptide widely distributed in mammalian tissues including the nervous system. The presence of this peptide in the nervous system likely plays a role in synaptogensis, axon growth, cell migration, and plastic changes in dendritic spine. However, the effects of Tbeta4 on the survival of neurons and axonal outgrowth have still not been fully understood. So far it is not clear if the effects of Tbeta4 are associated with L1 functions. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 65 publications
6
58
0
Order By: Relevance
“…Thus, it is possible that T4as-NPCs facilitate axonal regeneration by providing a growth-permitting guiding substrate through stimulation of the production of L1. Interestingly, a direct link between L1 and T4 has recently been shown in which T4 enhances L1 expression in a dose-dependent manner, and L1 mediates T4-induced neurite outgrowth and survival in neurons in vitro (Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that T4as-NPCs facilitate axonal regeneration by providing a growth-permitting guiding substrate through stimulation of the production of L1. Interestingly, a direct link between L1 and T4 has recently been shown in which T4 enhances L1 expression in a dose-dependent manner, and L1 mediates T4-induced neurite outgrowth and survival in neurons in vitro (Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…T4 plays a pivotal role in regulation of actin dynamics in neurons and is involved in cell survival and neurite elongation by influencing cytoskeleton changes and the redistribution of cell adhesion molecules (Yang et al, 2008). In particular, it has been proposed that T4 exerts its neuropromoting effects, at least partly, via mechanisms that involve activation of the cell adhesion molecule Journal of Cell Science 122 (22) L1.…”
Section: Transplanted T4as-npcs Survive and Differentiate In Injuredmentioning
confidence: 99%
“…In myocardial infarction animal model studies, Tβ4 was shown to promote the survival of cardiomyocytes and improve cardiac function [37]. Tβ4 has been found to be widely distributed in the mammalian central nervous system [15] [16] and it is expressed in most neural cell types of the developing brain and in subsets of neurons and microglia [17]. Exogenous Tβ4 has also been shown to promote the recovery of animals after ischemic stroke and brain trauma [18].…”
Section: Discussionmentioning
confidence: 99%
“…Tβ4 is widely distributed in the mammalian central nervous system [15] [16]. It is expressed in most neural cell types of the developing brain and in a subset of neurons and microglia [17]- [19]. Exogenous Tβ4 has been demonstrated to benefit the recovery of animals after ischemic stroke, traumatic brain injury (TBI), and experimental autoimmune encephalomyelitis (EAE) by stimulating OPCs [18] [20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…The logic of treatment is clear: early debridment of the secondary injury, thereby terminates its further expansion and reduces the pressure on the rest of the cord. Therefore I suggested the head of the Clinical Center of Spinal Cord Injury to practice early neurosurgery for patients of spinal cord contusion [8][9][10].…”
Section: Early Neurosurgery Of Spinal Cord Contusionmentioning
confidence: 99%